(untitled) (Baghdad Science Journal, 2012)
The amount of protein in the serum depends on the balance between the rate of its synthesis, and that of its catabolism or loss. Abnormal metabolism may result from nutritional deficiency, enzyme deficiency, abnormal secretion of hormones, or the actions of drugs and toxins. Renal cancer is the third most common malignancy of the genitourinary system, and accounts for 3% of adult malignancies globally. Total serum proteins were measured in malignant kidney tumor, benign kidney tumors, and non tumoral kidney diseases patient groups, as well as in healthy individuals. A significant decrease (p< 0.001) of total serum protein levels in patients with malignant kidney tumors when compared with those of benign tumors, non tumoral diseases, and healthy individuals. The lowest serum protein levels were found in patients with stage IV, regardless their genders. Analysis of total serum proteins using PAGE revealed clear differences in the number and shape of the bands in patients with different kidney diseases compared with healthy controls.